Management of neurotrauma during COVID-19: a single centre experience and lessons for the future. (3rd July 2021) - Manivannan, S.; Sharouf, F.; Mayo, I.; Albaqer, H.; Mehrez, M.; Jaber, H.; Nicholls, Z.; Woodward, B. O.; Watkins, W. J.; Zaben, M.
ABSTRACT: Introduction: Traumatic brain injury (TBI) is amongst the leading causes of morbidity and mortality worldwide. The unprecedented emergence of COVID-19 has mandated neurosurgeons to limit viral spread and spare hospital resources whilst trying to adapt management plans for TBI. We aimed to characterize how this affects decision-making on TBI management and drive strategies to cope with future expected waves. Methods: Retrospective TBI data collection from a single tertiary referral unit was performed between: 01/04/2019 – 30/06/2019 ('Pre-Epidemic') and 01/04/2020 – 30/06/20 ('Epidemic'). Demographics, mechanism of injury, TBI severity, radiological findings, alcohol/anticoagulants/antiplatelets use, and management decisions were extracted. Results: 646 TBI referrals were received in 'Pre-Epidemic' (N = 317) and 'Epidemic' (N = 280) groups. There was reduction in RTA-associated TBI (14.8 vs 9.3%; p = .04) and increase in patients on anticoagulants (14.2 vs 23.6%; p = .003) in the 'Epidemic' group. Despite similarities between other TBI-associated variables, a significantly greater proportion of patients were managed conservatively in local referring units without neurosurgical services (39.1 vs 56.8%; p < .0001), predominantly constituted by mild TBI. Conclusion: Despite COVID-19 public health measures, the burden of TBI remains eminent. Increases in local TBI management warrant vigilance from primary healthcare services to meet post-TBI needs in the community.